Assessment of Sclerodermoid Chronic Graft-versus-host Disease with Colour Doppler Ultrasound - Priscila Giavedoni; Carmen Martinez; Sebastian Podlipnik; María Suárez-Lleidó; Ignasi Martí-Martí; Daniel Morgado-Carrasco; Montserrat Rovira; Francesc Fernández-Avilés; Gonzalo Gutiérrez; Laura Rosiñol; Joan Cid; Miquel Lozano; et al. (Medical Journals Sweden, 2021)
Sclerodermoid chronic graft-versus-host disease (scGVHD) is a severe complication of allogeneic haema- topoietic stem cell transplantation. The aim of this study was to investigate the usefulness of high-frequency ultrasound of the skin in assessing the inflammatory patterns and prognosis of patients with scGVHD. A prospective study was carried out with patients who developed scGVHD in the period June 2016 to April 2018. Clinical and ultrasound examinations were performed on the first visit and at 6-month follow-up. A total of 24 patients were included in the study. A 6-month follow-up high-frequency ultrasound of the skin was performed on 20 of the 24 patients. Abnormal B-mode findings in high-frequency ultrasound of the skin consisted of hypoechogenic dermis, hypoechogenicity of septa and hyperechogenicity of lobules in hypodermis. No differences were observed in these basal parameters between treatment progressive/non-responding and inactive/responding scGVHD groups of patients. Basal Doppler showing increased vascular flow with a systolic peak ≥10 cm/s and a vascular resistance index ≥ 0.70 was observed only in those patients who developed progressive/non-responding scGVHD (62.5% vs 0% p = 0.006). In conclusion, Doppler ultrasound is a useful tool to assess the inflammatory activity and outcome of scGVHD. These findings could enhance patient management and help to guide treatment decisions.